Role of ABC-cassette transporters (MDR1, MRP1, BCRP) in the development of primary and acquired multiple drug resistance in patients with early and metastatic breast cancer - Kovalev, A.A.; Tsvetaeva, D.A.; Grudinskaja, T.V. (Experimental Oncology, 2013)
The aim of the research was to study the influence of multiple drug resistance (MDR1), multidrug resistance protein 1 (MRP1) and breast cancer resistance protein (BCRP) proteins expression on the effectiveness of chemotherapy in breast cancer (BC) patients. Patients and Methods: The retrospective analysis of the results of treatment of 77 women with invasive BC with different molecular subtypes at the age of 54.1±12.5, who received treatment in Zaporizhzhya Regional Clinical Oncological Dispensary during 2011–2013, has been carried out. 23 (29.8%) patients were in II stage of disease, 32 (41.5%) — in III stage, 22 patients (28.5%) — IV stage. Neoadjuvant therapy has been given to 34 (44.2%) patients, palliative therapy in connection with presence of hematogenous visceral and bone metastases — to 43 (55.8%) patients. Transport proteins BCRP, MRP and PGP have been studied in tissues of primary BC tumor, in tissues of visceral metastases, in metastatically altered regional lymph nodes, as well as in circulating in blood tumor cells (CTC). In every case, 1000 of tumor cells has been calculated. The intensity of staining (0, 1+, 2+, 3+), percentage of stained cells (threshold has constituted 10%) and homogeneity of tumor cells staining (homogeneous was considered 80% staining of cytoplasm or membrane of studied cells) has been taken in consideration. Results: Retrospective analysis has determined the dependence of results of polychemotherapy (PCT) on level and pattern of expression of BCRP, MRP and PGP proteins. In 1st group, in the absence thereof expression of transport proteins in BC cells, the objective response (CR + PR) from the tumor has been observed in 17 out of 18 patients (94.4%). In 2nd group (only cytoplasmic staining) the objective response has been observed in 36 patients (85.7%). Ineffectiveness of therapy and tumor progression in this group has been observed in 6 (14.2%) patients. In 3rd group (high membrane BCRP, MRP and PGP expression), in 14 out of 17 patients (82.3%), during the PCT occurred progression of the disease. Malignant phenotype of this tumor corresponded with the state of primary multiple drug resistance. In 80.0% of patients of this group, the neoadjuvant therapy turned out to be ineffective. Conclusion: Clinical trials for determination of role of ABC-transporters in the development of drug resistance of BC patients have not yet ended. The leading role in development of resistance of BC cells plays not only PGP, but also MRP1 and BCRP. Marker of resistance is not cytological, but membrane staining of cell.